Whole‐body MRI, including diffusion‐weighted imaging, for staging lymphoma: Comparison with CT in a prospective multicenter study. Issue 1 (31st October 2013) - Kwee, Thomas C.; Vermoolen, Malou A.; Akkerman, Erik A.; Kersten, Marie José; Fijnheer, Rob; Ludwig, Inge; Beek, Frederik J.A.; van Leeuwen, Maarten S.; Bierings, Marc B.; Bruin, Marrie C.A.; Zsíros, József; Quarles van Ufford, Henriëtte M.E.; et al.
Abstract : Purpose: To compare whole‐body magnetic resonance imaging (MRI), including diffusion‐weighted imaging (DWI), to computed tomography (CT) for staging newly diagnosed lymphoma. Materials and Methods: In all, 108 patients with newly diagnosed lymphoma prospectively underwent whole‐body MRI (T1‐weighted and T2‐weighted short inversion time inversion recovery [ n = 108], and DWI [ n = 104]) and CT. Ann Arbor stages were assigned according to whole‐body MRI and CT findings. Staging disagreements were resolved using bone marrow biopsy, FDG‐PET, and follow‐up studies. The results were descriptively analyzed. Results: Staging results of whole‐body MRI without DWI were equal to those of CT in 66.6%, higher in 24.1%, and lower in 9.3%, with correct/incorrect/unresolved higher staging and incorrect/unresolved lower staging relative to CT in 15/7/4 and 9/1 patient(s), respectively. Staging results of whole‐body MRI with DWI were equal to those of CT in 65.4%, higher in 27.9%, and lower in 6.7%, with correct/incorrect/unresolved higher staging and incorrect/unresolved lower staging relative to CT in 18/6/5 and 6/1 patient(s), respectively. Conclusion: The results of this study suggest that whole‐body MRI staging equals CT staging in the majority of patients with newly diagnosed lymphoma. No advantage of additional DWI was demonstrated. Whole‐body MRI can be a good alternative to CT if radiation exposure should be avoided.J. Magn. Reson. Imaging 2014;40:26–36 . ©2013 Wiley Periodicals, Inc .